2021
DOI: 10.1039/d0qm00649a
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding polypyrrole/carbon nanotube electrodes with high mass loading for robust flexible supercapacitors

Abstract: To meet the increasing requirement of flexible energy storage devices, it is critical to develop an electrode with commercial-level mass loading of active material for supercapacitors. Herein, we fabricated a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Notably, owing to the unique 3D helical morphology of CNC (the inset 2 of Figure 2b), the adjacent CNCs are in touch with each other via special point contact, which is distinguishing from the face contact between adjacent graphene sheets [32,33] and line contact between adjacent CNTs. [34,35] In contrast to the face and line contacts, the point contact between CNCs effectively prevents the agglomeration of CNCs [36,37] and consequently enhances the specific www.afm-journal.de www.advancedsciencenews.com…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, owing to the unique 3D helical morphology of CNC (the inset 2 of Figure 2b), the adjacent CNCs are in touch with each other via special point contact, which is distinguishing from the face contact between adjacent graphene sheets [32,33] and line contact between adjacent CNTs. [34,35] In contrast to the face and line contacts, the point contact between CNCs effectively prevents the agglomeration of CNCs [36,37] and consequently enhances the specific www.afm-journal.de www.advancedsciencenews.com…”
Section: Resultsmentioning
confidence: 99%
“…The high capacitance and the wide potential window of the device lead to an outstanding energy density of 211.4 μW h cm –2 (7.28 W h Kg –1 ) corresponding to a power density of 1 mW cm –2 (34.48 W kg –1 ), and a high power density of 5 mW cm –2 (172.4 W kg –1 ) at an energy density of 149.9 μW h cm –2 (5.16 W h kg –1 ) (Figure S22b, Supporting Information). Figure 7c and Table S7 in the Supporting Information further compare the overall energy storage performance of the as‐prepared device with those of some representative flexible solid‐state SCs based on carbon materials or conductive polymers, i.e., PPy/CNT, [ 87 ] NF/rGO/PPy, [ 33 ] rGO/PEDOT/PANI, [ 1 ] cellulose/rGO/Ag/Fe 2 O 3 , [ 88 ] PEDOT:PSS/MoS 2 , [ 89 ] rGO/MoO 2 /carbon textile, [ 90 ] ACFC/PANI/CNT/PANI, [ 91 ] and ANFs/MWCNTs/PANI. [ 63 ] It is concluded that the energy and power densities of our device are superior to the most of advanced flexible SCs reported previously in literatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, application of composites based on conducting polymers and carbon nanostructures for heavy metal sensing has been reviewed. [95] Such composites could also be used as electroactive materials in supercapacitors [96][97][98][99] and electrocatalysts in biologically-active compounds determination. [100][101][102]…”
Section: Discussionmentioning
confidence: 99%
“…Tremendous studies have exploring CNTs based fiber SCs corresponding to the fibrous structure nature of CNTs [102,103]. Other electroactive materials have also been exploded to compose with CNTs to fabricate fibrous structure for textile SCs and improve the electrochemical performance [104][105][106].…”
Section: Carbon Nanotubes Electrodes For Wscsmentioning
confidence: 99%